Transformasi Perdesaan: Kajian Fisik, Sosial Ekonomi, dan Laju Transformasi di Wilayah Peri Urban Surakarta - Aisyah Zahra; Iwan Rudiarto (P4W LPPM IPB, 2023)
The development of peri urban areas arise as a transition zone from rural into urban nature resulting the changes in characteristics of its area or commonly referred to as rural transformation. The rural transformation case has complexities indicated by the changes in terms of landscape and the shifts in terms of economic structure which previously was caused by the transformation from rural into urban. This research aims to analyze the characteristics which is resulted from the process in rural transformation at the border of Surakarta City, precisely in Colomadu District, and to analyze how fast the transformation is. The data in this research consist of physical aspects which are in the form of image and socio-economic characteristics. The quantitative descriptive analysis and spatial analysis are conducted in this research using remote sensing and map overlays. This research results that the transformation occurred between 2000 up to 2020 in Colomadu District showed significant development in urban characteristics. It is indicated by the shrinkage on agricultural land by 37% and the changes in the socio-economic activities of its society. Besides, there is also an uneven spreading on the rates of transformation in which the high transformation rates are found to be more dominant in those which directly adjacent to Surakarta City.